PENEGARUH PEMBERIAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL JAGUNG SEMI PADA TANAH PODSOLIK MERAH KUNING - Tania, Newar; -, Astina; Budi, Setia (Fakultas Pertanian Universitas Tanjungpura, 2012)
Research impact of gived biology feltilizer to growth and result of baby corn on podsolic red yellow soil was held at Surya Agro Tanjung Raya 2 St.Sungai Raya,Kubu Raya.during 69 days,from December 21,2011 until February 28,2012.This research was employed Complete Arrange Planned Methode that was 5 treatment and 5 repetitions,every repetitions fill 3 example of plant.Treatment that was gived into the plants is h0 (without tanotec) h1 (tanotec 1,1 ml/l) h2 (tanotec 3,3 ml/l) h3 (tanotec 5,0 ml/l) dan h4 (tanotec 6,6 ml/l).Parameter of this research is the high of the plant,length of corncob,diameter of corncob,and weight of corncob.The result of this research show that give biology feltilizer didn’t real impact toward research of the high of the plant ,length of corncob,diameter of corncob,and weight of corncob,because the sour element in the soil is low.Based on this research biology feltilizer treatment 6,6 ml/l dossis was showed higher result than all of other treatment it’s : high of plant 132,70 cm,length corncob 15,37 cm,diameter corncob 1,74 mm,and weight of corncob 40,02 gr/plants.